A delicious country : rediscovering the Carolinas along the route of John Lawson's 1700 expedition - Huler, Scott (The University of North Carolina Press, 2019)
"In 1700, John Lawson, a young man from England looking to make a name for himself, left London and landed in Charleston, in what is now South Carolina. From there for reasons still unknown he took a two-month journey through the little-known Carolina backcountry. That journey in 1709 yielded A New Voyage to Carolina, one of the great books about the Southeast in the early colonial period. Lawson wrote about the flora, the fauna, the terrain, and the native populations he visited, leaving behind descriptions unparalleled in the historical record. Lawson founded North Carolina's two first cities, Bath and New Bern, became the colonial surveyor general, and contributed scientific specimens to what has become the British Museum. In 1711, traveling among the Indians he knew and documented, Lawson was killed as the first casualty of the Tuscarora War. Despite his great contributions and remarkable history, Lawson is little remembered even in the Carolinas he documented. In 2014-15, Scott Huler for the first time retraced Lawson's path, encountering descendants of the settlers and native populations Lawson visited and comparing what he encountered with the country Lawson visited three centuries before. That richly documented journey has yielded this book"--